Validating Fitbit for Evaluation of Physical Activity in Patients with Knee Osteoarthritis: Do Thresholds Matter?. Issue 9 (11th October 2019) - Silva, Genevieve S.; Yang, Heidi; Collins, Jamie E.; Losina, Elena
Abstract : Objective: We sought to evaluate the performance of Fitbit in estimating ActiGraph‐derived moderate‐to‐vigorous physical activity (MVPA) and sedentary time in the knee osteoarthritis (OA) population. Methods: We used data from two weeks of Fitbit and ActiGraph wear among knee OA subjects. In primary analyses, we used literature‐based ActiGraph thresholds of 200 and 1924 counts/min (triaxial vector magnitude) for sedentary and MVPA time as the gold standard to which we compared three sets of Fitbit thresholds informed by literature and data (Youden index). We also considered personalized, stride length–based Fitbit thresholds. In sensitivity analyses, we used uniaxial, vertical axis–based as well as personalized, BMI‐based ActiGraph thresholds. We calculated agreement, sensitivity, and specificity of Fitbit in classifying sedentary and MVPA time. Results: In the primary analysis (vector magnitude thresholds), maximum agreement for sedentary and MVPA time was 67.0% from the Youden index–based and 91.1% from the stride length–based Fitbit thresholds. For sedentary time, the 20 strides/min threshold had the highest sensitivity (97.6%), and Youden‐derived 1 stride/min had the highest specificity (51.6%). For MVPA, Youden‐derived 14 strides/min yielded 72.8% sensitivity, and using stride length yielded 98.6% specificity. MVPA time ranged from 49‐323 min/d, depending on threshold used, with literature‐based and personalized thresholds leading to more conservative estimates of MVPA than Youden‐derived thresholds. Conclusion: Using Fitbit for MVPA and sedentary time assessment may lead to inaccurate estimates of both. Fitbit MVPA estimates were generally more conservative than ActiGraph estimates. Incorporating individuals' characteristics did not meaningfully improve Fitbit performance. Caution should be exercised when measuring activity using Fitbit.